Case reportNecrobiosis lipoidica diabeticorum – a case report - Kowzan-Korman, Alicja; Rosińska-Więckowicz, Anna; Olek-Hrab, Karolina; Czarnecka-Operacz, Magdalena; Silny, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Necrobiosis lipoidica diabeticorum is a very rare entity coexisting with diabetes. It is estimated that the prevalence of necrobiosis lipoidica is very low – it affects less than 1% of patients suffering from diabetes. Among patients with diagnosed necrobiosis lipoidica the percentage of those with diabetes is over 60%. This paper presents a case of a 16-year old girl with a 10-year history of insulin-dependent diabetes, in whom necrobiosis lipoidica was diagnosed